Pengaruh Greenwashing terhadap Brand Perception dan Keputusan Pembelian: Perspektif Konsumen pada Produk Berkelanjutan di Kota Bandung - sukandi, andi; Fazry, Rachma Waty (LPPM Akper Kebonjati, 2025)
This study aims to analyze the effect of greenwashing on consumer trust and purchasing decisions, and test the moderating role of environmentally sound consumer insights. Data were obtained through a survey of 304 respondents related to the consumption of products claimed to be environmentally friendly. The results showed that greenwashing has a positive and significant influence on consumer trust (β = 0.326, p < 0.05) and purchasing decisions (β = 0.358, p < 0.05), contrary to the initial hypothesis that expected a negative influence. In addition, environmentally sound consumer insights did not significantly moderate the relationship between greenwashing and consumer trust (β = -0.018, p > 0.05) or purchasing decisions (β = -0.007, p > 0.05). On the other hand, consumer trust in the brand was shown to have a positive and significant influence on purchasing decisions (β = 0.261, p < 0.05). This study makes an important contribution to the literature on greenwashing and consumer behavior, by showing that greenwashing-based marketing strategies can be positively received by consumers in certain contexts. The practical implication is that companies need to be careful in using greenwashing strategies and should place more emphasis on strengthening authentic brand trust to encourage purchase decisions.